Dieckol alleviates dextran sulfate sodium‐induced colitis via inhibition of inflammatory pathway and activation of Nrf2/HO‐1 signaling pathway. Issue 5 (17th December 2020) - Zhu, Xiaoyan; Sun, Yuanhua; Zhang, Ying; Su, Xinyou; Luo, Changqin; Alarifi, Saud; Yang, Hui
Abstract: Ulcerative colitis (UC) is the major type of inflammatory ailment with elevated prevalence worldwide. Dieckol (DEK) is a phlorotannin that is extensively found in marine algae and has been found to have different pharmacological properties. Nevertheless, the impact of DEK in UC has not been investigated earlier. Therefore, we appraised DEK's function in dextran sulfate sodium (DSS)‐induced UC in the mouse. An overall of 30 mice was randomized into 5 equal groups. Control mice treated with a standard diet (group I), colitis mice challenged with 3% of DSS through drinking water for 7 consecutive days (group II), DEK was supplemented via oral gavage from day 1 to 10 at the dosages of 5, 10, and 15 mg/kg b.wt, respectively. All animals were sacrificed on the 11th day. The body weight (bwt), colon length, disease activity index, malondialdehyde (MDA), myeloperoxidase (MPO), and histological features were observed using suitable techniques, and COX‐2 expression was investigated by immunohistochemistry. Moreover, TNF‐α, IL‐1β, p65, IκBα, HO‐1, and Nrf2 expressions were measured using ELISA and RT‐PCR techniques, respectively. DEK treatment to the colitis mice considerably lessened, DSS‐challenged alterations in body weight, DAI, colonic length shortening and histological changes. DEK exhibited potent antioxidant effects due to the reduced MDA and MPO, and Nrf2 expression markers while the HO‐1 marker was augmented. Additionally, DEK also suppressed the expression s of TNF‐α, IL‐1β, and the p‐p65, p‐IκBα, and p65 and augmented the expression of IκBα, which eventually proved the anti‐inflammatory potential of DEK against the DSS‐challenge. Based on these results, DEK has been found effective in mitigating colitis, conceivably alleviating colon inflammation through the NF‐κB inhibition and triggering of Nrf2/HO‐1 signaling cascade.